Analysis of the Effect of Product Innovation as an Effort to Develop Culinary Variants on Consumer Satisfaction (Case Study: Baked Steamed Bread in Bajeng District) - Tuti Supatminingsih; Muhammad Dinar; Marhawati; Andi Asti Handayani; Hikmayani Subur (Formosa Journal of Social Sciences (FJSS), 2023)
Entrepreneurship is a way or effort to take advantage of opportunities by applying innovation in business development. This research aims to determine the development of culinary variants on consumer satisfaction in the Baked Steamed Bread Business in managing the business so that it is able to compete and survive in running the business. This research uses quantitative methods. The research in the article shows the results of a simple linear regression analysis which proves that product innovation has an effect on consumer satisfaction at the Baked Steamed Bread Business in Bajeng District. This can be seen from the constant value of 23,156 and the X regression coefficient value of 0.471, which states that the consumer satisfaction value has increased by 0.471. This means that the direction of influence of variable X on Y is positive